LOCAL COMMUNITY-BASED DIGITAL LIBRARY SERVICES - Hazan Hazan; Nur Ainun Musa; Misnawati Misnawati; M. Nur Rahmat Achdar HT; Andi Mudassir (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2025)
This study explores community-based digital library services in Bone Regency, South Sulawesi, focusing on how participatory design and user needs mapping shape innovation and impact. Using a qualitative case study with 15 informant. data were collected gathered through observation, semi-structured interviews and document analysis. Findings show that digital libraries have introduced service innovations such as online portals, mobile applications, and digitized local knowledge developed through active user participation and periodic evaluation. The services are used for academic, research, and community literacy purpose but challenges persist, including infrastructure constraints, low digital literacy, and limited human resources. Despite these constraints, the services foster improved access to information, cultural preservation, and stronger community collaboration. The novelty of this study lies in integrating Community-Based Design and Information Needs Assessment to highlight how rural digital libraries can become inclusive, innovative, and sustainable. Practical implications and directions for further research are also discussed to encourage the development of more inclusive, innovative, and sustainable digital library services.